The Effect of Carbon Price Volatility on Firm Green Transitions: Evidence from Chinese Manufacturing Listed Firms - Xintong Wu; Zhendong Li; Fangcheng Tang (Energies, 2022)
Accelerating the promotion of the green transition can help to achieve high-quality development in manufacturing industries. In terms of policies that encourage the transition to green production, carbon trading is a direct and effective means of achieving this goal, and the carbon price is an important regulator in trading. Normally, firms respond to carbon prices by making three behavioral choices: production restrictions, pollution reduction, and the technological transition to green production. This study examines the effect of carbon price volatility on the decision to conduct green production, i.e., transforming to sustainable technologies and processes. In addition, this paper also investigates whether organizational resource slack and organizational technical standards moderate the relationship between the carbon price volatility and firms’ green transitions. The results suggest that a steadily increasing carbon price will motivate firms to make a green transition, but if the carbon price is volatile, firms will be reluctant to make a green transition. This tendency to make a green transition is stronger when firms have resource slack and have implemented green technical standards. The findings provide empirical evidence and policy implications regarding how manufacturing firms can accelerate their green transition.